Exophthalmos, Diplopia, and Bilateral Eyelid Edema: Symptoms of Ocular Mastocytosis. Issue 11 (November 2016) - Payerols, Arnaud; Frouin, Eric; Schiffmann, Aurélie; Menjot de Champfleur, Nicolas; Canioni, Danielle; Chandesris, Olivia; Costes, Valérie; Villain, Max; Mura, Frédéric
ABSTRACT: Purpose: Mastocytosis is characterized by clonal mast cell proliferation with accumulation within various organs and uncontrolled activation with excessive mast cell mediator release. Ocular manifestations have rarely been published. We describe a 63-year-old man with bilateral exophthalmos that led to the diagnosis of systemic mastocytosis. Case Report: A patient presented with bilateral eyelid edema with exophthalmos associated with binocular diplopia. Ophthalmologic examination showed bilateral axial, symmetrical, and painless exophthalmos with eyelid edema, and limitation in elevation of the right eye. Visual acuity was normal. Orbital magnetic resonance imaging showed increased volume of both the superior and medial recti muscles and right inferior oblique muscle, and histopathological examination of orbital fat and muscle biopsies revealed an infiltration by mast cells. Serum tryptase was elevated. The patient also complained of a long history of pruritis and diffuse skin erythema that could be elicited with just mild pressure (Darier's sign). A bone marrow biopsy confirmed the infiltration of abnormal mast cells with a D816V mutation in the KIT gene. Treatment with cladribine was initiated and resulted in resolution of both ocular and systemic signs and symptoms that persisted without relapse 18 months after discontinuation. Ocular mastocytosis is a rare condition, which was previously reported to involve the conjunctiva, cornea, uvea, eyelid, orbit, and choroid. Cases of ocular mastocytosis can be classified into two main groups: mast cells tumors (mastocytomas) and ocular manifestations associated with systemic mastocytosis. Histological examination of ocular samples is rarely performed, and there are no standard criteria for the diagnosis of ocular mastocytosis. Our case emphasizes cladribine could represent an alternative treatment. Conclusions: Our case is the first published case of exophthalmos and eyelid edema associated with systemic mastocytosis confirmed by pathologic examination of periocular biopsies that was treated effectively with cladribine.